Efficacy of benzimidazole anthelmintics in goats and sheep in the Philippines using a larval development assay - Ancheta, P.B.; Dumilon, R.A.; Venturina, V.M.; Cerbito, W.A.; Dobson, R.J.; LeJambre, L.F.; Villar, E.C.; Gray, G.D. (Elsevier, 2004)
The negative effects of nematodes in small ruminants can be reduced by use of dewormers but their effectiveness is increasingly limited by the emergence of anthelmintic resistance. The efficacy of benzimidazole (BZ) anthelmintics in the Philippines was estimated by an in vitro larval development assay using worm eggs recovered from faeces collected from goats and sheep. Two hundred and eighteen farms were selected to represent areas of the country with high goat and sheep populations and the full range of farm sizes, from smallholders with just a few animals to commercial and institutional farms with several hundred. Initial surveys of worm control advisers indicated that BZs have been in continuous widespread use for up to 20 years with little use of other chemical groups. A larval development assay (LDA: DrenchRite(R)) was modified for use with BZs alone to allow up to five samples to be analysed on a single microtitre plate. The assay was validated by comparison with the faecal egg count reduction test (FECRT). The dominant nematode genera were Haemonchus and Trichostrongylus with small numbers of Oesophagostomum.The range of BZ efficacy estimated from the LDA results was 0-100% and the distribution of efficacy levels was continuous, with mean efficacy of 82 and 64% for goats and sheep, respectively. There were significant associations between efficacy and parameters measured to characterize the sampled farms: size of animal management group, FEC of sample, recent importation of stock and no access to common grazing were all correlated with decreased efficacy. Likewise, low efficacy was associated with reported frequency and number of years that BZ drenches had been used.The LDA was found to be highly suited to estimate efficacy in nematode populations from small farms where performance of a FECRT for even one chemical would be impractical. Using a larval development assay, we have demonstrated a wide efficacy range for BZs against nematodes from all sizes of goat and sheep farms in the tropics.